Brake squeal analysis in time domain using ABAQUS - Finite element simulation of brake squeal for passenger cars - Keshavarz Kelachayeh, Mir Arash (My University, 2017)
One of the main quality concerns of car manufacturers is brake squeal. There are two CAE (Complex Aided Engineering) method for prediction of brake squeal, CEA (Complex Eigenvalue Analysis) and TDA (Transient Dynamic Analysis). However, CEA method is a quite usual tool to evaluate brake squeal propensity despite its intrinsic overestimation of any system instabilities. In contrast, TDA provides a reduced number of predicted instabilities, but it is too time consuming for complete FE models. The purpose of this thesis is the comparison of TDA with CEA to identify brake squeal frequencies. The finite element model of studied brake system consists of a brake disc, and pair of brake pads (friction material and backplate). Using the CEA method, brake squeal frequencies are identified by coalescence modes and calculation of Negative Damping Ratio (NDR) for various pressure and friction coefficient. As a comparison with CEA, TDA is performed by use of dynamic explicit solver to extract the variation of amplitude at a node on the brake disc friction surface over time. The frequency response function of a node on brake disc can be calculated by Discrete Fourier Transform (DFT), the frequencies correspond to the peaks of frequency response function can be considered as a representative of brake squeal frequency. The comparison of TDA and CEA reveals that even though five modes are introduced by NDR criteria for brake squeal onset, merely two of them are detected by TDA. Taking account of CEA overestimation about unstable modes, it can be concluded that the frequency response derived from the transient response can be a reliable method to represent the system instability. In addition, regarding TDA results brake squeal might happen in an unstable mode even with low value of real part as well as NDR. Key words: Brake, squeal, complex eigenvalue analysis, transient Dynamic analysis, stability
Keywords: Teknisk mekanik; Farkostteknik; Applied Mechanics; Vehicle Engineering